EXTREME HEAT, SOCIAL VULNERABILITY, AND RESPIRATORY HEALTH IN KANSAS: A CENSUS TRACT-LEVEL ANALYSIS - Haas, Sierrah (My University, 2023)
Extreme heat poses a significant threat to several aspects of human health through the impact of physical, social, and environmental risk factors. Reducing the impact of extreme heat is crucial to promoting health for all. Research has shown associations between rising global temperatures and negative respiratory health outcomes. Temperatures in Kansas have been rising steadily and are predicted to continue to do so. Drastic changes in temperature without ample time for human acclimation results in certain populations being more highly vulnerable to its effects. This preliminary study was conducted with the goal of geographically identifying populations most vulnerable to extreme heat in Kansas. This identification was done using readily available extreme heat, social vulnerability, and respiratory illness data. The data were analyzed and interpreted using geographic information system (GIS) mapping. Census tract- level data were visually explored to identify areas showing potentially associated extreme heat rates and COPD or asthma crude prevalence. Furthermore, using social vulnerability data, populations that are more likely to need related resources were identified. Results indicated that 49.5% of census tracts that are considered highly socially vulnerable show a higher crude prevalence of chronic obstructive pulmonary disease (COPD) and asthma. Also, 30% of these census tracts fall within geographic areas with a higher-than-average number of annual days with recorded extreme heat conditions. Findings concluded that social vulnerability is a potential determinant of respiratory health. Future work is a necessity in improving respiratory health in areas with high rates of extreme heat. Exploring social vulnerability data in this context allows for a more targeted approach to this work.
Keywords: Asthma; Chronic Obstructive Pulmonary Disease; Social Vulnerability; Extreme Heat; Respiratory Health